Ismailism and Islam in modern South Asia - Mukherjee, Soumen. (Cambridge, United Kingdom ; New York)
xiii, 203 sayfa
Keywords: “Explores the evolution of a Shia Ismaili identity in modern South Asia and traces the genealogies of conceptual categories and institutions that conditioned the historical process.“ --